2009
DOI: 10.1080/08858190902924849
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Cancer Management: At What Cost to Medical Student Education?

Abstract: Advances in patient management has resulted in a shift to ambulatory care reducing patient accessibility. Medical schools must identify means to provide students with adequate patent exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This may in part explain the lack of interest in oncology by Australian medical students, as only 68% were taught oncology theoretically and clinically, 79% were dissatisfied with the number of teaching hours, and 68% were dissatisfied with their level of clinical exposure. A study that found that Australian medical interns in 2006 had less opportunity to examine cancer patients than interns did in 1990 [ 5 , 6 ]. These data raise a question whether the oncology education provided by Australian universities is of sufficient quality and quantity to gain the interest of students and to make them feel confident that they have the knowledge and skills required to enter the specialty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may in part explain the lack of interest in oncology by Australian medical students, as only 68% were taught oncology theoretically and clinically, 79% were dissatisfied with the number of teaching hours, and 68% were dissatisfied with their level of clinical exposure. A study that found that Australian medical interns in 2006 had less opportunity to examine cancer patients than interns did in 1990 [ 5 , 6 ]. These data raise a question whether the oncology education provided by Australian universities is of sufficient quality and quantity to gain the interest of students and to make them feel confident that they have the knowledge and skills required to enter the specialty.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that oncology is underrepresented in the curricula of Australian medical schools, and concern has been raised regarding the extent of the exposure of students to oncology [ 5 ]. McRae et al [ 5 ] compared the cancer knowledge and skills of interns graduating from graduate medical program courses with those from non–general medical program courses and also compared the cancer knowledge and skills of interns in 2001 with those who completed a similar survey in 1990 [ 6 ] and concluded that graduates from 2001 had less exposure to specific cancers such as melanoma, rectal cancer, and mouth cancer than those who trained in 1991. The study was guided by the Australian Cancer Society’s Ideal Oncology Curriculum for Medical Schools, which was established in 1999 and has been regularly updated, with the last revision in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is the leading global cause of mortality 1,2 . Despite this, cancer education and oncology patient exposure is often lacking in medical schools, resulting in interns who are underprepared for interactions with cancer patients [3][4][5][6][7][8] . By the age of 85, one in two males and one in three females in Australia will be diagnosed with cancer 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer control is multidisciplinary yet education about cancer in universities is often split by tumour site and discipline. Education is made more heterogeneous by its delivery in diverse clinical schools and more recently by the development of rural clinical schools that may have limited access to oncology facilities . The majority of clinical teaching is performed by conjoint appointments who have limited training as educators and light supervision.…”
mentioning
confidence: 99%
“…Education is made more heterogeneous by its delivery in diverse clinical schools and more recently by the development of rural clinical schools that may have limited access to oncology facilities. 8 The majority of clinical teaching is performed by conjoint appointments who have limited training as educators and light supervision. Competition for curriculum time is intense especially in post graduate courses that have been apparently truncated to 4 years.…”
mentioning
confidence: 99%